ANNIE SULLIVAN'S MOTIVES OF TEACHING HELEN KELLER IN NADIA TASS'S THE MIRACLE WORKER MOVIE: A HUMANISTIC PSYCHOLOGICAL PERSPECTIVE - PERMATASARI, DYAH (2011)
The major problem of this research is to explain motives of Annie Sullivan in teaching Helen Keller reflected in Nadia Tass's The Miracle Worker movie. Objectives of this research are: to analyze the movie based on its structural elements, and to analyze movie based on Humanistic Psychological Perspective theory by Abraham Harold Maslow. In conducting this research, the researcher uses qualitative research, in which the primary data is taken from The Miracle Worker movie and the secondary data is taken from other data related to the research such as some books of Humanistic Psychological Perspective theories, movie script, commentaries, internet and other relevant information. This research comes to the following conclusions. First, based on the structural analysis of the movie, it shows that the character and characterization, setting, plot, point of view, theme, mice en scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on Humanistic Psychological Perspective analysis that is some motives underlying the struggle of Annie Sullivan. The motives are getting safety in the job, family, respected by others and the last motive is to actualize the potential as a teacher.